Implementasi Tata Kelola Keuangan Pendidikan dalam Program ‘Aje Kendor Sekolah’ Kota Serang - Farda Fahira; Laeli Nur Khanifa; Nisaul Istiqomah; Juwita Siregar; Azizah Vara Ramadhansyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The implementation of educational financial management is crucial as part of the commitment to progress that is the focus of this study, with the aim of examining financial management based on the principles of effectiveness, efficiency, transparency, and accountability in the 'Aje Kendor Sekolah' program using Public Financial Management Theory and Policy Implementation Theory. This study uses a qualitative research method with Creswell's case study approach. The research findings indicate that budget management aligns with formal procedures, but planning is not yet fully participatory. The reporting system is structured, but community involvement in oversight remains symbolic. The presence of collaboration among various stakeholders has not addressed the shortages in facilities and funding. Therefore, these shortages need to be addressed to encourage sustained school participation in the future.